THE ROLE OF DESIGN OBJECTS IN CREATING THE VISUAL IDENTITY OF A CITY BASED ON THE CULTURAL HERITAGE OF CHINA - Liu , Q.; Shmelova-Nesterenko , O. (Art and Design, 2023)
The purpose: to investigate and analyze the current situation regarding the integration of Chinese cultural heritage into design objects aimed at creating the city’s image, substantiating the necessity of such integration in modern conditions. Methodology. The research used the methods of literature review, synthesis, analysis, and systematization of the obtained results. Additionally, a situational analysis of the visual image of Chinese sports events is conducted. Results. The importance and necessity of integrating aesthetic elements of Chinese cultural heritage into the design production of the city’s visual identity are justified. Future research directions in this field are identified. The study analyzes successful examples of design objects for major sports events in China developed using cultural heritage elements. Scientific novelty. The study involves the analysis and synthesis of previous research on the topic. Based on this analysis, four promising directions for further research in the field of design production for creating the urban image are identified. Practical significance. The findings of this research can be applied in studying innovative design based on cultural heritage and in practical design of objects visualizing the urban image.